Exploring the Intersection Between Informal Carers’ Experiences, Digital Poverty and Poor Socioeconomic Status, Protocol - Peter Sunny Blaney; Oladayo Bifarin; Mikolaj Zarzycki; Pooja Saini; Rosanna Cousins (BJPsych Open)
Aims: In 2021–2022, 10.5% of UK citizens provided unpaid informal care, saving the government £162 bn annually. Many carers reside in high-deprivation areas, where access to appropriate health and social care services is limited. Previous studies indicate that carers are more prone to depression, anxiety, and physical symptoms, and these negative outcomes are higher among socio-economically disadvantaged carers. The shift of some health and social care services online, combined with ‘digital poverty’ (having no suitable electronic devices with Internet access or limited access or skills concerning the Internet), may exacerbate difficulties with accessing health and social care support, potentially increasing unmet needs and burdens among socioeconomically disadvantaged carers. The aim is to understand how informal carers with marginalised socioeconomic status (SES) access existing health and social care services and how this impacts their mental health. The second aim of the project is to explore how potential digital poverty may shape a carer’s mental health outcomes.